Lokasyon bazlı mobil pazarlama uygulamalarının tüketici satın alma davranışları ile ilişkisi üzerine bir araştırma - Kurtaran, Başak (My University, 2019)
Mobil Pazarlama, Lokasyon Bazlı Mobil Pazarlama, Tüketici Davranışı, Satın Alma, Mobil Pazarlama Uygulamaları

Teknolojinin gelişmesiyle akıllı telefonlar ve diğer mobil cihazlar kolay ulaşılabilir ve kullanılır hale gelmiştir. Bu durum mobil pazarlama alanı olarak yeni bir pazarlama kanalının oluşmasına olanak sağlamıştır. Kotler’e göre her yeni teknoloji ‘yaratıcı imha’ olan bir güçtür. Şirketleri rakiplerden ziyade yeni teknolojiler zorlamaya başlayacaktır.Mobil pazarlama, tüketicilerin asıl ihtiyaç ve ilgili oldukları konularda çeşitli tanıtım ve pazarlama faaliyetlerinin yapılmasına olanak sağlamıştır. Üretici firmalar açısından mobil pazarlama ise asıl hedef kitlelerine ulaşmak ve geri dönüş oranları üzerinden ölçüm yapmak için doğru pazarlama enstürmanlarını kullanmasına imkan vermiştir. Çalışmamda lokasyon bazlı mobil pazarlama uygulamalarını kullanan müşteriler ele alınarak, bu uygulamalar üzerinden satın alıma yönelik gönderilen bildirimlerin satın alma eylemine teşvik edip etmediğini ve tüketicilerin genel tutumları araştırılacak olup gelecekte bu tarz teknolojik pazarlamaya yatırım yapıp yönelmek isteyen şirketlere ışık tutacaktır. Bu konuda yapılacak araştırmalara da emsal nitelikle olacaktır. ABSTRACT With the development of technology, smartphones and other mobile devices have become easily accessible and available. Thus, new marketing channel is mobile marketing is created. According to Kotler, every new technology is a force that is ‘creative destruction’.Companies will begin to push new technologies to get better than competitors. Mobile marketing provides technological services, marketing, saving, and according to the actual request and related promotion and marketing activities. The manufacturer-oriented mobile marketing company is able to use the right marketing instruments to ensure that it is metered to its target audience and return system.The mobile marketing message provide significant advantages to today's marketers if it is sent to the right person at the right time. Location based mobile marketing is a mobile marketing method that introduces the brand by directing the 6 customers to buy the customers in the region where the customers share the location using the instant location information.Companies know they need to turn. But adapting to today's consumer revolution is part of the challenge. To stay relevant, you must know where the world goes tomorrow. The next wave of interruptions will affect our lives in ways we can't even imagine today. The question that is not possible in the past, but with a much more targeted audience with today's technology, can be reached by people, the question to be asked is what consumers think about it. If consumers generally have positive attitudes towards to location based advertising, then this technology may be new marketing communication channel to get better company. In my study, customers using location based mobile marketing applications will be addressed and whether the notifications sent for purchase via these applications encourage the buying action and the general attitudes of consumers will be investigated and will shed light on the companies that would like to invest in this kind of technological marketing in the future. The researches on this subject will be preceded by a precedent. Mobile Marketin, Location based Marketing, Customer Behaviours
Keywords: Consumers; Lokasyon Bazlı Pazarlama Location Based Marketing; Marketing; Pazarlama; Purchasing; Satın alma; Tüketiciler